EEG Changes across Multiple Nights of Sleep Restriction and Recovery in Adolescents: The Need for Sleep Study - Ong, Ju Lynn (Sleep, 2016)
STUDY OBJECTIVES: To investigate sleep EEG changes in adolescents across 7 nights of sleep restriction to 5 h time in bed [TIB]) and 3 recovery nights of 9 h TIB. METHODS: A parallel-group design, quasi-laboratory study was conducted in a boarding school. Fifty-five healthy adolescents (25 males, age = 15–19 y) who reported habitual TIBs of approximately 6 h on week nights (group average) but extended their sleep on weekends were randomly assigned to Sleep Restriction (SR) or Control groups. Participants underwent a 2-week protocol comprising 3 baseline nights (TIB = 9 h), 7 nights of sleep opportunity manipulation (TIB = 5 h for the SR and 9 h for the Control group), and 3 nights of recovery sleep (TIB = 9 h). Polysomnography was obtained on two baseline, three manipulation, and two recovery nights. RESULTS: Across the sleep restriction nights, total SWS duration was preserved relative to the 9 h baseline sleep opportunity, while other sleep stages were reduced. Considering only the first 5 h of sleep opportunity, SR participants had reduced N1 duration and wake after sleep onset (WASO), and increased total sleep time (TST), rapid eye movement (REM) sleep, and slow wave sleep (SWS) relative to baseline. Total REM sleep, N2, and TST duration remained above baseline levels by the third recovery sleep episode. CONCLUSIONS: In spite of preservation of SWS duration over multiple nights of sleep restriction, adolescents accustomed to curtailing nocturnal sleep on school day nights evidence residual effects on sleep macro-structure, even after three nights of recovery sleep. Older teenagers may not be as resilient to successive nights of sleep restriction as is commonly believed. CITATION: Ong JL, Lo JC, Gooley JJ, Chee MW. EEG changes across multiple nights of sleep restriction and recovery in adolescents: the need for sleep study. SLEEP 2016;39(6):1233–1240.